PSS on OCB with Work Engagement as a Mediating Variable - Khairina, Umul; Trinanda, Okki (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
With work engagement serving as a mediating variable, this study intends to examine the relationship between perceived supervisor support and organizational citizenship behavior among Kawat Asa Teknik Utama Factory employees. A quantitative approach using a census technique on a sample of 40 employees is the research method employed. Questionnaires that have undergone validity and reliability testing were distributed in order to collect data. Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method was used to analyze the data. The study's findings demonstrated that 1) Organizational Citizenship Behavior is positively and significantly impacted by perceived supervisor support. 2) Work engagement is positively and significantly impacted by perceived supervisor support. 3) Organizational Citizenship Behavior is positively and significantly impacted by work engagement. 4) The connection between perceived supervisor support and organizational citizenship behavior is positively and significantly mediated by work engagement.